Domain specificity of creativity - Baer, John, 1948- (Amsterdam : Academic Press, 2015)
Recent research findings have challenged the idea that creativity is domain-general. Domain Specificity of Creativity brings together the research information on domain specificity in creativity -- both the research that supports it and answers to research arguments that might seem to challenge it. The implications for domain specificity affect how we move forward with theories of creativity, testing for creativity, and teaching for creativity. The book outlines what these changes are and how creativity research and applications of that research will change in light of these new findings.
Chapter 7 -- Finding Common Ground: The APT Model of Creativity and Metatheoretical Approaches to Understanding CreativityComposite Theories; Metatheories; Conclusions; References; Subject Index; Back Cover.
Foreword Chapter 1. Domain Specificity: Introduction and Overview Chapter 2. Research Evidence for Domain Specificity Chapter 3. Implications of Domain Specificity for Creativity Theory Chapter 4. Implications of Domain Specificity for Creativity Research Chapter 5. Implications Of Domain Specificity for Creativity Assessment Chapter 6. Implications of Domain Specificity for Creativity Training Chapter 7. Finding Common Ground: The APT Model of Creativity and Metatheoretical Approaches to Understanding Creativity.
CIP data; item not viewed.
Includes bibliographical references and index.
Keywords: Creative ability; Creative ability; Electronic books; Electronic books